2005
DOI: 10.1007/s10495-005-1323-3
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint and physiological apoptosis in germ cells proceeds normally in spaceflown Caenorhabditis elegans

Abstract: It is important for human life in space to study the effects of environmental factors during spaceflight on a number of physiological phenomena. Apoptosis plays important roles in development and tissue homeostasis in metazoans. In this study, we have analyzed apoptotic activity in germ cells of the nematode C. elegans, following spaceflight. Comparison of the number of cell corpses in wild type or ced-1 mutants, grown under either ground or spaceflight conditions, showed that both pachytene-checkpoint apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 26 publications
2
31
0
Order By: Relevance
“…We also confirmed the same results as Nelson found: protons and gamma rays have different effects on C. elegans gene pattern through GO analysis. Short term (10 d) exposure to actual space radiation and microgravity on ICE-FIRST revealed that apoptosis proceeds normally [9] and that no significant increase in the rate of mutation occurs [10]. Decreased levels of myogenic transcription factor were observed [27].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We also confirmed the same results as Nelson found: protons and gamma rays have different effects on C. elegans gene pattern through GO analysis. Short term (10 d) exposure to actual space radiation and microgravity on ICE-FIRST revealed that apoptosis proceeds normally [9] and that no significant increase in the rate of mutation occurs [10]. Decreased levels of myogenic transcription factor were observed [27].…”
Section: Discussionmentioning
confidence: 98%
“…The effects on nematodes that were grown for 3 -4 generations in CeMM media and in space for 10 d were analyzed. In this experiment, space-faring animals underwent normal development, apoptosis [9], and DNA repair [10], but experienced altered muscle development [11]. Because it can sustain a high degree of radiation damage, C. elegans can be used as a potential biological dosimeter [12].…”
Section: Introductionmentioning
confidence: 99%
“…For exposures below 40 Gy, most damage to the meiotic nuclei of C. elegans can be repaired by the meiotic homologous recombination system [Takanami et al, 2000[Takanami et al, , 2003. Apoptotic cell corpses in the pachytene region of dissected gonads were visualized by differential interference contrast microscopy [Deng et al, 2004;Higashitani et al, 2005;Sugimoto et al, 2006].…”
Section: Smf Administration and Ir Irradiationmentioning
confidence: 99%
“…Moreover, because worms are easy to handle, studies using C. elegans have been conducted in space. Worms survive and grow well in space, and many functions of the worms are normal (Higashitani et al, 2005; Szewczyk et al, 2008; Zhao et al, 2006). Muscle gene expression is slightly altered in space (Higashibata et al, 2006), as well as markers for aging (Honda et al, 2012).…”
Section: Introductionmentioning
confidence: 99%